2015
DOI: 10.1108/ijrdm-07-2014-0097
|View full text |Cite
|
Sign up to set email alerts
|

Selling luxury goods online: effects of online accessibility and price display

Abstract: Purpose – Luxury goods manufacturers have long been hesitant to adopt the internet as a channel of distribution. A luxury brand’s concept of exclusiveness is seemingly incompatible with the ubiquitous accessibility provided by the mass medium internet. The purpose of this paper is to address the apparent contradiction by examining consumer responses to the online accessibility and price display of luxury goods. Design/methodology/approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 29 publications
(46 reference statements)
3
43
1
Order By: Relevance
“…This result gains support from the previous study that consumers' trust allows the firms to become more confident in selling their products, which implies on pricing capability (Konuk, 2015). To fully maintain pricing capability in the social relationship context, firms need to be economically viable (Kluge and Fassnacht, 2015).…”
Section: Mrrsupporting
confidence: 72%
See 1 more Smart Citation
“…This result gains support from the previous study that consumers' trust allows the firms to become more confident in selling their products, which implies on pricing capability (Konuk, 2015). To fully maintain pricing capability in the social relationship context, firms need to be economically viable (Kluge and Fassnacht, 2015).…”
Section: Mrrsupporting
confidence: 72%
“…In a high-pressure business environment, a salesperson may be tempted to use hard selling approaches, which may undermine a company's ability to build long-lasting relationships with its customers based on trust (Guenzi et al, 2016). Firms with premium price need to be economically viable to fully maintain trust and pricing capability in the social relationship context (Kluge and Fassnacht, 2015).…”
Section: Mediating Effect Of Selling Capabilitymentioning
confidence: 99%
“…A study of luxury wristwatch manufacturers found that communication and interactivity tools were used on a large scale (Barbosa et al, 2013). Thus, despite the reluctance of many luxury brands to move many of their customer-facing activities online, there appears to be growing consensus that luxury brands find value in using the Internet and social media platforms to achieve their strategic goals (Kluge and Fassnacht, 2015). Thus, a second consideration for luxury firms is whether they will use the capabilities of the Internet to engage in one-way or two-way communication.…”
Section: Luxury Firms and The Internet Dilemmamentioning
confidence: 99%
“…On the other hand, shoppers may not be purchasing online because of some potential risks related with Internet shopping including credit card fraud, an absence of touch before buying the product, possible problems with the returned goods (Bhatnagar, Mishra & Rao, 2000) and not receiving the ordered product (Forsythe & Shi, 2013;Joines, Scherer & Scheufele, 2003). For consumers, buying of luxury goods online has raised some concerns, regarding the lack of touch (Kluge & Fassnacht, 2015;Pappas, 2016), security (Wu, Chen & Chaney, 2013;Liu, Burns & Hou, 2013). To understand typology of Korean millennials' attitudes toward online luxury purchasing behavior, this study provides the following three components: 1) attitude; 2) luxury consumption; and 3) online shopping.…”
Section: Typology Of Online Luxury Consumersmentioning
confidence: 99%